SINTESIS LAPISAN TIPIS TiO2 BERPORI YANG DIMODIFIKASI OLEH NITROGEN DENGAN METODE PEROKSO SOL-GEL, KARAKTERISASI DAN APLIKASINYA SEBAGAI MATERIAL PEMBERSIH DIRI (SELF CLEANING MATERIAL) - Wellia, Diana Vanda (Jurnal Riset Kimia, 2016)
The photocatalytic properties of TiO2 compound in anatase phase can be activated under visible light by nitrogen modification and its ability can be increased by generated porous structure using polietilen glikol (PEG) on TiO2 thin film surface. The porous N/TiO2 thin films were prepared by heating aqueous peroxotitanate thin films by addition of polietilen glikol (PEG) deposited uniformly on superhydrophilic uncoated glass at 500 oC for 1 h. The result of X-ray diffraction (XRD) confirmed the resence of only anatase phase for all samples. The UV-Vis spectroscopy showed the synthesized porous N/TiO2 thin films exhibit the absorption in the visible range (400-500 nm). Photocatalytic activity of porous N/ TiO2 thin films were evaluated by using fourier transform-infrared spectroscopy (FTIR) to determine the ability of this photocatalyst for stearic acid degradation under visible light irradiation. The result showed that N/TiO2/PEG-2.1 thin film degraded the stearic acid was about 87,86%, which was 1,12 times higher than that of N-doped TiO2 and 9,9 times higher than that of undoped TiO2 thin film.